Development and Psychometric Evaluation of the Patients’ Educational Expectations Scale - Emine Akçin Şenyuva (Journal of Nursing Measurement, 2026)
Background and Purpose: Understanding patients’ educational expectations is essential for delivering effective, patient-centered education in clinical settings. However, the absence of a psychometrically robust instrument limits the systematic assessment of these expectations. This study aimed to develop and psychometrically evaluate the Patients’ Educational Expectations Scale (PEES). Methods: Data were collected from 301 patients. Exploratory factor analysis (EFA; principal axis factoring with oblique rotation) was conducted on one subsample ( n = 150), followed by confirmatory factor analysis (CFA) on an independent subsample ( n = 151) using a split-sample validation approach. Alternative models, including single-factor and second-order structures, were tested to evaluate model fit and structural robustness. Convergent validity and discriminant validity were assessed using composite reliability, average variance extracted, and the Fornell–Larcker criterion. Internal consistency was examined using coefficient alpha and McDonald’s omega, and test–retest reliability was assessed over a 15-day interval. Results: EFA revealed a theoretically coherent four-factor structure explaining 59.23% of the total variance. CFA indicated acceptable to good model fit (χ² to degree of freedom ratio = 2.412; root mean square error of approximation = .069; comparative fit index and Tucker–Lewis index within acceptable thresholds). The four-factor model demonstrated superior fit compared with the single-factor model, and second-order CFA supported a hierarchical structure. Composite reliability values exceeded .70 across factors, and discriminant validity was confirmed. The total scale showed excellent internal consistency (α = .95), with omega coefficients supporting reliability. Test–retest results indicated strong temporal stability. Conclusions: The PEES is a psychometrically sound, multidimensional instrument for assessing patients’ educational expectations. Its validated structure, reliability, and stability support its use in clinical practice and research. The scale has strong potential to facilitate patient-centered education planning and evaluation in nursing contexts.